Clinical effectiveness of space maintainers and space regainers in the mixed dentition: A systematic review - Khaled Khalaf; Aseel Mustafa; Mohammad Wazzan; Mennatalla Omar; Mohammed Estaitia; Mohamed El-Kishawi (Elsevier, 2022)
Background: The aim of this systematic review was to address the clinical effectiveness of space maintainers and space regainers in the prevention and correction of dental arch decreases in mixed dentition. Methods: An electronic search was conducted using five databases: the Cochrane Database for Systematic Reviews, EBSCO Host, ScienceDirect, PubMed, and Scopus (until February 2021) and 6 relevant journals. Inclusion criteria were: Randomized Controlled Clinical Trials (RCTs), Controlled Clinical Trials (CCTs), cohort studies and case-control studies of children in the mixed dentition requiring a space maintainer or a space regainer, children with mild to moderate crowding, and with Class I and mild Class II or Class III skeletal pattern. All articles included in this review were examined independently by three teams of investigators to assess the level of bias using the Cochrane risk of bias tools RoB 2.0 (for RCTs) and ROBINS-I (for non-RCTs). Results: Following the three phases of a systematic search, 11 studies were included for the final analysis, of which nine used space maintainers (a lower lingual arch) and two used space regainers (one lip bumper and one transpalatal arch) with contradicting results. Four of the former and one of the latter devices showed a significant increase in arch length. Out of the 11 articles, one was found to be of critical risk, two of serious risk and eight of moderate risk of bias. Conclusions: There is very low evidence to suggest that space maintainers and regainers are effective in preserving arch length and preventing mild to moderate crowding in children during the mixed dentition stage at the expense of lower incisor proclination. However, considering the low evidence provided by this systematic review, high-quality studies are needed.